A Case Report of Placenta Percreta - Widiana Ferriastuti; Dwi P. R. Tampubolon; Qonita Qonita (Humanistic Network for Science and Technology (HNST), 2021)
There has been an increased incidence of placenta accreta in recent decades, which is associated with an increase in cesarean delivery. A woman aged 39 years GIVP1111 at 8 months of gestation was a breech location with antepartum bleeding et. causa placenta previa totalis suspected percreta bladder infiltration and hematuria. The last abdominal ultrasound showed no visible clot retention and mild right-sided hydronephrosis (possibly a physiological condition). Due to doubts regarding the suspicion of placental invasion of the bladder, an MRI examination of the abdomen was performed. A network was irregular in shape and can not be oriented either right or left, some of which have been split. Attached to the placenta. It was not clear that the cervix and bladder were visible, the total weight was 500 grams, the size was 15x13x5 cm. Based on both macroscopic and microscopic histopathological examinations, it could be concluded that the uterus, adnexa, surgery: placenta percreta, adenomyosis uteri. Keywords: placenta percreta; uterus; antepartum bleeding